Lower Kolyma multilingualism: Historical setting and sociolinguistic trends. (August 2021) - Pupynina, Maria; Aralova, Natalia
Aims and objectives/purpose/research questions: The region of Lower Kolyma (LK), Russia, exhibits a unique multilingual situation which involves five languages from five different families: Even (Tungusic), Yakut (Turkic), Chukchi (Chukotko-Kamchatkan), Tundra Yukaghir (Yukaghir), and Russian (Slavic, Indo-European). Our research aims to show the ongoing changes in this setting and to explain the historical background of these trends. Design/methodology/approach: Our approach combines the results of a sociolinguistic survey, published data about the history and ethnography of the region, and observed linguistic effects of language contact. Data and analysis: The sample for our sociolinguistic study includes 196 individuals, born between 1878 and 1996. To assess the patterns of multilingualism we use two parameters: the number of acquired languages and the composition of the linguistic repertoires. To model the linguistic situation in the 20th century, an average life span parameter is used. Findings/conclusions: We demonstrate that in 1940 to 1980 it was most common for LK residents to use all languages of the region. Partly, at least, this was a consequence of the introduction of boarding schools, which became an additional domain for interethnic communication. In recent decades we observe a tendency for a shift to Russian with a concomitant decrease in speakers of the minority languages. Originality: We use an approach of retrospective interviews which allows us to cover a large time period and to provide an overview of changes in the multilingual setting during the 20th century. Thus, even though multilingualism in this area has already been discussed by Vakhtin, the methodological approach is different. Significance/implications: The paper contributes to the field of sociolinguistics, presenting a new case study of multilingualism from an area of Siberia which is understudied in this regard.